Properties of Self-Compacting Concrete with Coal Bottom Ash Under Aggressive Environments - Mohd Haziman, Wan Ibrahim; Shahiron, Shahidan; Algaif, Hassan Amer; Ahmad Farhan, Hamzah; Putra Jaya, Ramadhansyah (Springer, 2021)
This book highlights the importance of incorporating coal bottom ash (CBA) into self-compacting concrete exposed to aggressive conditions. The incorporation of CBA in concrete is a sustainable strategy to prolong the lifespan of concrete. The content of the book is also regarded as a solution to the environmental issue. It helps academics, researchers, and students to acquire a better understanding of the influence of coal bottom ash on the properties of concrete through four sequential chapters. The book first presents background information on concrete deterioration, and then the improvement in properties of self-compacting concrete with different percentages of CBA exposed to tap water, sulphate solution, chloride solution, and seawater.